Mediterranean Diet Patterns in Relation to Lung Cancer Risk: A Meta-Analysis - Du, Hongzhen; Cao, Tengrui; Lu, Xuning; Zhang, Tianfeng; Luo, Bin; Li, Zengning (Frontiers in Nutrition, 2022)
Background: This study aims to systematically quantify the association between Mediterranean diet patterns and the risk of lung cancer, because the results of the study are not consistent. Methods: Researchers searched PubMed and Web of Science databases to find all articles before October 2021. The Newcastle-Ottawa (NOS) scale was used to assess the quality of research. A random effects model was used to estimate aggregate hazard ratios (HRs) and 95% confidence intervals (CIs). Due to the significant heterogeneity, we performed subgroup analysis, Meta regression analysis, and sensitivity analysis. When data were available, a dose-response analysis was also performed. Results: A total of 9 articles were included for meta-analysis. Meta-analysis shows that there is a significant negative correlation between the Mediterranean diet pattern and the risk of lung cancer in the population: hazard ratio (HR)=0.82, 95% confidence interval (95%CI)=0.74-0.92, high heterogeneity (I2 = 59.9%, P<0.05). Due to the significant heterogeneity, we conducted subgroup analysis, meta regression analysis, and sensitivity analysis, and found that the type of study design was the source of heterogeneity. Sensitivity analysis showed that the final results did not change much, the sensitivity was low, and the results were relatively stable. Finally, the dose-response relationship shows that on the basis of the lowest Mediterranean diet score (0 points), for every 3 points increase, the risk of lung cancer is reduced by 9%. Conclusions: The evidence in this meta-analysis shows that there is a significant negative correlation between the Mediterranean diet and the risk of lung cancer, suggesting that the Mediterranean diet is a protective factor for lung cancer.